The Existence of Self-Control in Students During Language Learning Activities in the Context of Islamic Religious Education - Novita Fitri Amin (Universitas Al-Amien Prenduan, 2022)
This research aims to explore the role of self-control in language learning activities within the scope of Islamic Religious Education. The study employs a qualitative approach with a literature review type focusing on scholarly works addressing the topic. The data sources include scholarly literature such as reference books and published journal articles. Content analysis is utilized as the data analysis method. The results of this research indicate that self-control plays a crucial role in shaping character, improving the quality of learning, and achieving Islamic educational goals. The integration of self-control in the context of Islamic education not only contributes to academic achievements but also to the development of a robust and sustainable Islamic character.